INTERNET CULTURE AND E-LIFESTYLE: PENERAPAN KOMUNIKASI DAN TEKNOLOGI DI MEDIA BARU DALAM MENDUKUNG PEMBANGUNAN NASIONAL - Afdoli Ramadoni, Muhamad; Nuha Nabila Aswari; Abu Hanifah; Muhammad Zainuddin Nawi; Titin Yenni; Kurniati Rezki Fitra (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2024)
In the era of globalization, communication technology is developing rapidly. This started with the discovery of the first technology that had an influence on human life. These technological advances have changed little by little the lifestyle and behavior of our society. The internet continues to develop until finally it gives birth to new media which refers to emphasizing cultural forms and contexts in computers. In Indonesia, the development of information and communication technology is growing rapidly. The role of society is very large in technological development. Technology shapes individuals in various ways of thinking, behaving in society and ultimately technology directs humans to move from one century to another. Technological developments have brought major changes to human behavior, both in the political, social, economic and even cultural fields. In this case, researchers try to determine the formation of public information and the massification of information as a result of technological developments which ultimately give rise to new media. This research analyzes using the theory of Socio-Cultural Change. Communication and technology are one of the factors that influence socio-cultural change. Social change has three dimensions, namely: structural, cultural and interactional. First, the structural dimension refers to changes in the structure of society. Second, the cultural dimension refers to cultural changes in society. Third, the interactional dimension refers to changes in social relations in society. The research results show that humans use the concept of new technology to refer to the emergence of a technology that has an important impact on social life. Technology becomes an instrument to achieve goals. In the end, the existence of technology is used as a tool to achieve the goals of human life.